Synovial cytokines significantly correlate with osteoarthritis-related knee pain and disability: inflammatory mediators of potential clinical relevance - Nees, Timo A.; Rosshirt, Nils; Zhang, Jiji A.; Reiner, Tobias; Sorbi, Reza; Tripel, Elena; Walker, Tilman; Schiltenwolf, Marcus; Hagmann, Sébastien; Moradi, Babak (Journal of Clinical Medicine, 2019)
The aim of this study was to identify inflammatory mediators of potential clinical relevance in synovial fluid (SF) samples of patients with knee osteoarthritis (OA). Therefore, radiographic OA severity, knee pain and function of 34 OA patients undergoing unicompartmental (UC) and bicompartmental (BC) knee arthroplasty were assessed prior to surgery and SF samples were analyzed for a broad variety of inflammatory mediators, including interleukins (ILs), interferons (IFNs), C-X-C motif ligand chemokines (CXCLs), and growth factors (nerve growth factor; NGF, vascular endothelial growth factor; VEGF, and stem cell growth factor β; SCGF-β) using multiplex assay. Significant differences were observed between the SF levels of different inflammatory markers. When compared to UC OA, significantly higher concentrations of IL-7, IL-8, IL-10, IL-12, IL-13, IFN-γ, VEGF and CXCL1 were detected in BC OA. Correlation analyses revealed significant associations between OA severity and IL-6, IL-8, IFN-γ, SCGF-β, VEGF, CXCL1. Interestingly, increases in both anti- (IL-10, IL-13) and pro-inflammatory (IL-7, IL-12, IFN-γ) cytokines, as well as growth factors (SCGF-β, VEGF), correlated significantly with the level of knee pain. Poorer knee function was associated with higher IL-6, IL-10, IL-12, IL-13, IL-18, βNGF, SCGF-β, VEGF and CXCL9 levels. In conclusion, this study provides an extensive profile of synovial inflammatory mediators in knee OA and identifies cytokines of potential clinical relevance. In fact, five of the mediators examined (IL-10, IL-12, IL-13, SCGF-β, VEGF) significantly correlate with both knee pain and function.
Gesehen am 19.02.2020